Secularism and early religious plurality. Methodists and secular state in the 1880s (Quinto Sol, 2015)
This article focuses on the performance of Argentine Methodists in a critical period, that of the 1880s, when the debate on secularism of state institutions brought the religious question to the forefront and Methodists made an effort to become spokespersons of an active and visible Protestant minority. It postulates that Protestant presence throughout the nineteenth century, and especially Methodist militancy in the 1880s, are essential for understanding the early plural conformation of the Argentine religious field and the characteristics of its particular brand of laicity.
Keywords: Protestantism; Methodism; secularism; religious plurality